2015
DOI: 10.1377/hlthaff.2014.0483
|View full text |Cite|
|
Sign up to set email alerts
|

Medicare Annual Preventive Care Visits: Use Increased Among Fee-For-Service Patients, But Many Do Not Participate

Abstract: Under the Affordable Care Act (ACA), Medicare coverage expanded in 2011 to fully cover annual preventive care visits. We assessed the impact of coverage expansion, using 2007-13 data from primary care patients of Medicare-eligible age at the Palo Alto Medical Foundation (204,388 patient-years), which serves people in four counties near San Francisco, California. We compared trends in preventive visits and recommended preventive services among Medicare fee-for-service and Medicare health maintenance organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 9 publications
2
55
0
Order By: Relevance
“…Chung and colleagues evaluated Medicare beneficiaries in a large multispecialty practice and found that colorectal cancer screening rates had declined slightly, though perhaps less than expected, among Medicare fee-for-service beneficiaries. 20 A series of reports published by the Department of Health and Human Services concluded that the absolute number of Medicare beneficiaries using preventive services has increased. 21,22 Most recently, Fedewa et al examined colorectal cancer screening use before and after passage of the ACA and found a modest increase in use, particularly among the poor and elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Chung and colleagues evaluated Medicare beneficiaries in a large multispecialty practice and found that colorectal cancer screening rates had declined slightly, though perhaps less than expected, among Medicare fee-for-service beneficiaries. 20 A series of reports published by the Department of Health and Human Services concluded that the absolute number of Medicare beneficiaries using preventive services has increased. 21,22 Most recently, Fedewa et al examined colorectal cancer screening use before and after passage of the ACA and found a modest increase in use, particularly among the poor and elderly.…”
Section: Discussionmentioning
confidence: 99%
“…We did not fully assess HRA implementation including how characteristics of the care delivery setting affect data management capacity [35]. As CMS provides financial incentives for the annual wellness visit, our findings reflect PRO implementation in response to external incentives rather than internal needs [36]. We focused on data collection and use and did not examine clinician attitudes towards using these PROs at the point of care or patients’ perceptions of response burden or usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, assessing and acting on patient-reported information may not change individual or population-level scores of the measures themselves. 27,34,42,43 Thus it may be the process of PRO assessment and clinical action that reflects high-quality care and not necessarily the change in PRO score. This interpretation of PRO use is consistent with calls for "reimagining" quality assessment to focus on measuring important processes, with less emphasis on outcomes.…”
Section: Discussionmentioning
confidence: 99%